2006
DOI: 10.4067/s0717-95022006000500023
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Impact of Various Assessment Parameters on the Medical Students Performance in the Professional Anatomy Examination in a New Medical School

Abstract: There is a dearth of knowledge on the level of agreement between all the various assessment tasks on the same content area, in order to test this hypothesis we adopted the concept of convergent validity and also to isolate area of academic weakness among the students and to readjust the curriculum content to balance the weakness. A blinded cohort retrospective study was carried out on a total of sixty-six third year medical students who had sat for their first professional examination in anatomy in the new med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The anatomy spotter exam has several aliases in the literature: it is also referred to as the bell ringer format (Aziz et al, 2014), anatomy steeplechase (Inuwa et al, 2011a;Shaibah and van der Vleuten, 2013;Pratten et al, 2014) or simply anatomy practical exam (Lukić et al, 2001;Poljičanin et al, 2009;Severo and Tavares, 2010). The spotter is described as an exam in which wet specimens, plastic models, bones, histological slides and imaging are used, prepinned with labels/flags, and there are between 30 (Schubert et al, 2009;Sagoo et al, 2016) and 40-50 (Shittu et al, 2006;Inuwa et al, 2011a) such stations. Each station has 1-2 questions relating to the pinned material, which students are given time (40 sec to 1 min) to answer.…”
Section: Types Of Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomy spotter exam has several aliases in the literature: it is also referred to as the bell ringer format (Aziz et al, 2014), anatomy steeplechase (Inuwa et al, 2011a;Shaibah and van der Vleuten, 2013;Pratten et al, 2014) or simply anatomy practical exam (Lukić et al, 2001;Poljičanin et al, 2009;Severo and Tavares, 2010). The spotter is described as an exam in which wet specimens, plastic models, bones, histological slides and imaging are used, prepinned with labels/flags, and there are between 30 (Schubert et al, 2009;Sagoo et al, 2016) and 40-50 (Shittu et al, 2006;Inuwa et al, 2011a) such stations. Each station has 1-2 questions relating to the pinned material, which students are given time (40 sec to 1 min) to answer.…”
Section: Types Of Assessmentmentioning
confidence: 99%
“…Questions range from basic identification of structures to ones of application and function. Some ask students to select the correct answer from a list of five options (MCQ style) (Schubert et al, 2009;Inuwa et al, 2011a;Ikah et al, 2016), while others do not specify whether MCQ questions or free text responses are utilized (Lukić et al, 2001;Shittu et al, 2006;Poljičanin et al, 2009;Severo and Tavares, 2010). MCQs generate higher mean scores than questions using the free text response format, possibly because of the cueing effect (Shaibah and van der Vleuten, 2013).…”
Section: Types Of Assessmentmentioning
confidence: 99%
“…Therefore, final examination grades may correlate more with final MCQs scores. It was also reported that MCQs can be used to test remembering domain and considered to be a good predictor of a student's performance in other elements of anatomical assessment [19].…”
Section: Bdsmentioning
confidence: 99%
“…In Bangladesh, medical education is centrally controlled by the Government and run a unique undergraduate curriculum throughout the country in both public and private sectors. The present official form of undergraduate medical curriculum has first evolved in 1988 followed by revision in 2002 and 2012 [7]. In the undergraduate medical curriculum of 2002 of Bangladesh, extensive modification of the assessment system was done.…”
Section: Introductionmentioning
confidence: 99%